A composite autotrophic nitrogen removal and phosphorus removal filter material and its preparation method and application
By preparing a composite autotrophic nitrogen removal filter for furilic acid chelated iron ion modified hydrotalcite composite adsorbent and sulfaaluminate cement components, the problems of low efficiency and high cost of nitrogen removal in traditional technology are solved. It achieves efficient and low-cost nitrogen and phosphorus removal in water, adapts to the water self-raising denitrification environment, and extends the life of the filter material.
Patent Information
- Application Number
- CN202411077031.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-08-07
AI Technical Summary
Traditional deammonia and phosphorus removal technologies have problems such as low efficiency, high cost, and sludge generation, which are difficult to effectively solve the eutrophication phenomenon of water bodies caused by excessive nitrogen and phosphorus emissions in water bodies.
The preparation method of composite autotrophic nitrogen removal filter material is adopted, by redispersible glue powder, sustained-release adsorbent, sodium thiosulfate, clay, sulfur, sulfur aluminate cement, ferrous sulfate, silica fume, etc. The components are mixed and the furiac chelated iron ion modified hydrotalcite composite adsorbent is prepared by rapid carbonization and permanent condensation spraying. Combined with sulfur autotrophic denitrification process, the pH value is adjusted, and the adsorption capacity and phosphorus removal performance are improved.
It significantly improves the removal rate of nitrogen and phosphorus in water, extends the service life of the filter material, reduces operating costs, adapts to the growth environment of sulfur autotrophic denitrification bacteria, and improves the efficiency and sustainability of nitrogen removal and phosphorus removal. sex.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of autotrophic denitrification and dephosphorization filter materials, in particular to a composite autotrophic denitrification and dephosphorization filter material and a preparation method and application thereof. Background Art
[0002] With the acceleration of urbanization and the increase of industrial activities, water pollution is becoming increasingly serious, especially the eutrophication of water bodies caused by excessive discharge of nitrogen and phosphorus nutrients. This not only affects the balance of the aquatic ecosystem, but may also cause serious environmental problems such as algal blooms and red tides, thereby threatening the survival of aquatic organisms and human health.
[0003] Traditional technologies for deammonification and phosphorus removal include biological methods, chemical precipitation methods, and physical adsorption methods. These methods have some limitations in practical applications. For example, biological methods have strict requirements on water environment conditions and limited treatment efficiency; although chemical precipitation methods are effective quickly, they will produce a large amount of sludge and secondary pollution; physical adsorption methods require frequent replacement of adsorption materials and have high operating costs.
[0004] Therefore, it is of great significance to find an efficient, low-cost and sustainable composite autotrophic nitrogen and phosphorus removal filter material. Summary of the invention
[0005] The object of the present invention is to provide a composite autotrophic nitrogen and phosphorus removal filter material and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material comprises the following steps:
[0008] S1: adding redispersible rubber powder and slow-release adsorbent into deionized water and stirring evenly to obtain a binder;
[0009] S2: adding sodium thiosulfate, clay and sulfur into deionized water and stirring evenly, adding a binder, granulating, aging and drying at room temperature to obtain slow-release adsorption particles;
[0010] S3: adding sulphoaluminate cement, ferrous sulfate and silica fume into deionized water and stirring evenly to obtain a concrete premix; mixing the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry;
[0011] Furthermore, the sulphoaluminate cement was purchased from Zhengzhou Wanglou Cement Industry Co., Ltd.; the chemical components, by mass percentage, included 11.17% SiO 2 、25.83%Al 2 O 3 、2.64%Fe2 O 3 , 43.94% CaO, 1.03% MgO, 9.73% SO 3 1.02% TiO 2 .
[0012] S4: adding the mixed slurry into a mold, drying, and curing the solidified material to obtain a composite autotrophic denitrification and dephosphorization filter material.
[0013] Furthermore, the preparation method of the sustained-release adsorbent comprises the following steps: adding chitosan microspheres to a 1% v / v acetic acid solution, heating to 30-32° C. and stirring to swell, ultrasonically dispersing fulvic acid chelated iron ion modified hydrotalcite in deionized water to obtain a suspension; adding the suspension to the chitosan microsphere acetic acid solution, stirring for 24-26 hours, washing with deionized water, centrifuging, and vacuum drying to obtain a sustained-release adsorbent;
[0014] Furthermore, the concentration of the suspension is 1 mg / mL; in the sustained-release adsorbent, the mass ratio of chitosan microspheres to fulvic acid chelated iron ion modified hydrotalcite is (1-1.5):1.
[0015] Furthermore, the preparation method of the chitosan microspheres comprises the following steps: adding chitosan to a 3% v / v acetic acid solution and stirring evenly to obtain an aqueous phase; adding paraffin to the aqueous phase, adding Span 80, heating to 40-45° C. and emulsifying for 1.5-2 hours under light-proof conditions, adding glutaraldehyde and continuing the reaction for 2-2.5 hours, washing the reaction solution with petroleum ether and isopropanol alternately for 3-4 times, and vacuum drying the reaction solution at 50-55° C. for 24 hours to obtain chitosan microspheres;
[0016] Furthermore, the concentration of the aqueous phase is 0.5-1 g / 100 mL; the volume ratio of aqueous phase to paraffin is 3:1.
[0017] Furthermore, the preparation method of the fulvic acid chelated iron ion modified hydrotalcite comprises the following steps: adding fulvic acid to a 0.25M sodium hydroxide solution and stirring evenly to obtain a sodium fulvic acid solution; adding magnesium chloride hexahydrate and aluminum chloride hexahydrate and stirring evenly to deionized water to obtain a metal ion solution; under a nitrogen atmosphere, adding the metal ion solution and a 0.5M sodium hydroxide solution to the sodium fulvic acid solution and stirring evenly, adjusting the pH to 8-10, heating to 80-85°C and allowing to react for 12-14 hours, centrifuging, collecting the precipitate, washing with deionized water, and vacuum freeze-drying to obtain fulvic acid modified hydrotalcite; grinding the fulvic acid modified hydrotalcite and ultrasonically dispersing it in deionized water, adding a ferric nitrate solution, reacting for 2-2.5 hours, filtering, washing, and grinding to obtain fulvic acid chelated iron ion modified hydrotalcite;
[0018] Furthermore, the concentration of the sodium fulvic acid solution is 1-1.5 g / 100 mL; in the metal ion solution, the molar ratio of magnesium ion: chloride ion is 2:1, and the magnesium ion concentration of the metal ion solution is 0.32-0.4 M / 100 mL; in the fulvic acid-modified hydrotalcite, the mass ratio of metal ion solution solute: sodium fulvic acid solution solute is 4:2; the concentration of the ferric nitrate solution is 1.5-2 g / 100 mL; in the fulvic acid-chelated iron ion modified hydrotalcite, the mass ratio of fulvic acid-modified hydrotalcite: ferric nitrate solution solute is (3-4):1.
[0019] Furthermore, the components in the binder include 20-30 parts of dispersible rubber powder, 10-15 parts of slow-release adsorbent, and 55-70 parts of deionized water, calculated by weight.
[0020] Furthermore, the components in the slow-release adsorption particles include, by weight, 20-60 parts of sodium thiosulfate, 30-40 parts of clay, 5-35 parts of sulfur, 12-20 parts of binder, and 15-25 parts of deionized water.
[0021] Furthermore, the components in the concrete premix include 250-300 parts of sulphoaluminate cement, 10-12 parts of ferrous sulfate, 25-30 parts of silica fume, and 85-95 parts of deionized water in terms of mass fraction; the mass ratio of the slow-release adsorption particles to the concrete premix is (1-3):1.
[0022] Furthermore, the post-treatment curing process includes rapid carbonization of the solidifying material and spraying of the permanent setting liquid; wherein the rapid carbonization process includes placing the solidifying material in a rapid carbonization box with a 20% concentration of carbon dioxide for carbonization for 7-28 days; the permanent setting liquid spraying process includes spraying the surface of the solidifying material after rapid carbonization 2-3 times, and the spraying time is 3-7 days.
[0023] The invention discloses a composite autotrophic denitrification and dephosphorization filter material, which is prepared by a preparation method of the composite autotrophic denitrification and dephosphorization filter material.
[0024] The application of the composite autotrophic denitrification and phosphorus removal filter material is used in the sulfur autotrophic denitrification and phosphorus removal process.
[0025] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0026] The invention uses magnesium chloride hexahydrate and aluminum chloride hexahydrate as raw materials, and synthesizes a fulvic acid-modified hydrotalcite composite adsorbent by coagulation and adsorption bridging with fulvic acid macromolecules during the coprecipitation of hydrotalcite crystal nuclei; and then utilizes the property that the hydroxyl group in the fulvic acid structure can chelate iron ions to prepare the fulvic acid-chelated iron ion modified hydrotalcite. On the one hand, there is a synergistic adsorption interaction in the process of simultaneously adsorbing nitrogen and phosphate by the fulvic acid-modified hydrotalcite composite adsorbent. When the composite adsorbent adsorbs phosphate, the Zeta potential decreases and the adsorption attraction for nitrogen increases. When the Zeta potential increases after adsorbing nitrogen, the adsorption of phosphorus can be promoted, which greatly improves the adsorption capacity of the hydrotalcite. The modification of hydrotalcite with fulvic acid increases the surface negative charge density and further improves the nitrogen adsorption capacity of the hydrotalcite modified with fulvic acid chelated iron ions. On the other hand, by using fulvic acid chelated iron ions, iron ions are introduced into the hydrotalcite modified with fulvic acid chelated iron ions, and the iron ions are used to react with the soluble phosphates in the sewage to form insoluble phosphate precipitates, thereby further improving the phosphorus removal performance of the hydrotalcite modified with fulvic acid chelated iron ions.
[0027] Since the optimal pH of the bacterial community in the sulfur autotrophic denitrification process is between 6.8-8.2, the denitrification efficiency will decrease rapidly when the pH is below 6.5 or above 9; the fulvic acid chelated iron ion modified hydrotalcite prepared by the present invention has similar range requirements for pH for the technical effect of denitrification and phosphorus removal. When the pH increases, the adsorption sites on the surface of phosphate and hydrotalcite will be electrostatically repelled, and the negatively charged hydroxide ions will also compete with sulfate for adsorption, resulting in a decrease in the adsorption rate; when the pH decreases, hydrogen ions will compete with nitrogen for adsorption, reducing the nitrogen removal rate. Most traditional composite autotrophic denitrification and phosphorus removal filter materials use cement as a skeleton, resulting in a higher pH of the filter material itself. The pH of traditional silicate cement is between 12-13, which is not conducive to the rapid growth of sulfur autotrophic denitrification bacteria, nor is it conducive to the denitrification and phosphorus removal adsorption of hydrotalcite.
[0028] The present invention selects aluminum sulfate cement as the cement raw material and dopes it with silica fume and ferrous sulfate. On the one hand, the aluminum sulfate cement has a lower alkalinity. On the other hand, the hydrogen ions generated in the sulfur autotrophic denitrification process are used to promote the dissolution of aluminum ions and iron ions in the aluminum sulfate cement, maintain the pH balance of the system and generate phosphate precipitation at the same time, thereby achieving the effect of improving phosphorus removal. The synergistic rapid carbonization (using carbon dioxide to interact with alkaline hydration products in the cement hydration process to achieve the purpose of reducing alkalinity) and the spraying of the permanent setting liquid (using water-soluble silicate to replace alkanes to react with calcium hydroxide in cement to generate insoluble crystals to achieve the purpose of reducing alkalinity) work together to maintain the pH of the composite autotrophic denitrification and phosphorus removal filter material at about 9 after the maintenance is completed, and to ensure that the sulfur autotrophic denitrification and phosphorus removal filter material can reproduce rapidly in the early stage of use and quickly enter the state of denitrification and phosphorus removal; in order to ensure that the composite autotrophic denitrification and phosphorus removal filter material has excellent denitrification and phosphorus removal effects in the early stage of use, that is, during the entire use process, the hydrotalcite is coated with chitosan to achieve a slow release effect, so that the filter material can undertake the task of assisting denitrification and phosphorus removal in the early stage, and assist the sulfur autotrophic denitrification and phosphorus removal bacteria in the later stage, thereby greatly improving the service life and application range of the composite autotrophic denitrification and phosphorus removal filter material. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following examples, the redispersible rubber powder model is 5004N, purchased from Wacker Chemie; the permanent setting liquid model is W-type DPS, purchased from Shanghai Xuanhong Waterproof Technology Co., Ltd.; the other raw materials are commercially available.
[0031] Preparation method of chitosan microspheres: add 0.5g chitosan to 100mL 3% v / v acetic acid solution and stir evenly to obtain an aqueous phase; add paraffin to the aqueous phase, add 1.2wt% Span 80, heat to 40°C and emulsify for 1.5h under light-proof conditions, add 1mL glutaraldehyde and continue to react for 2h, use petroleum ether and isopropanol to wash the reaction solution alternately for 3 times, place the reaction solution at 50°C and vacuum dry for 24h to obtain chitosan microspheres;
[0032] The preparation method of fulvic acid chelated iron ion modified hydrotalcite is as follows: fulvic acid is added to 0.25M sodium hydroxide solution and stirred evenly to obtain 1g / 100mL sodium fulvic acid solution; magnesium chloride hexahydrate and aluminum chloride hexahydrate are added to deionized water and stirred evenly to obtain a metal ion solution with a magnesium ion concentration of 0.32M / 100mL and a chloride ion concentration of 0.16M / mL; under a nitrogen atmosphere, the metal ion solution and 0.5M sodium hydroxide solution are added to the sodium fulvic acid solution and stirred evenly, the pH is adjusted to 9, heated to 80°C and allowed to react for 12h, centrifuged, the precipitate is collected, washed with deionized water, and vacuum freeze-dried to obtain fulvic acid modified hydrotalcite; 1.5g of fulvic acid modified hydrotalcite is ground and ultrasonically dispersed in 100mL deionized water, 100mL of 0.5g / 100mL ferric nitrate solution is added, reacted for 2h, filtered, washed, and ground to obtain fulvic acid chelated iron ion modified hydrotalcite;
[0033] In the fulvic acid-modified hydrotalcite, the mass ratio of the metal ion solution solute to the sodium fulvic acid solution solute is 4:2.
[0034] The preparation method of the sustained-release adsorbent is as follows: 100 mg of chitosan microspheres are added to a 1% v / v acetic acid solution, heated to 30°C and stirred for swelling, 100 mg of fulvic acid chelated iron ion modified hydrotalcite is ultrasonically dispersed in 100 mL of deionized water to obtain a suspension; the suspension is added to the chitosan microsphere acetic acid solution, stirred for 24-26 hours, washed with deionized water, centrifuged, and vacuum dried to obtain a sustained-release adsorbent.
[0035] Example 1: A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: 20 parts of redispersible rubber powder and 10 parts of slow-release adsorbent are added to 70 parts of deionized water and stirred evenly to obtain a binder;
[0036] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 12 parts of a binder are added, granulated, aged and dried at room temperature to obtain slow-release adsorption particles;
[0037] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 1:1;
[0038] S4: adding the mixed slurry into the mold, drying, and curing the solidified material, placing the solidified material in a rapid carbonization box with 20% concentration of carbon dioxide for carbonization for 7 days, spraying the surface of the solidified material after rapid carbonization twice, and the spraying time is 3 days to obtain a composite autotrophic denitrification and phosphorus removal filter material.
[0039] Example 2: A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: 20 parts of redispersible rubber powder and 15 parts of slow-release adsorbent are added to 65 parts of deionized water and stirred evenly to obtain a binder;
[0040] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 12 parts of a binder are added, granulated, aged and dried at room temperature to obtain slow-release adsorption particles;
[0041] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 1:1;
[0042] S4: adding the mixed slurry into the mold, drying, and curing the solidified material, placing the solidified material in a rapid carbonization box with 20% concentration of carbon dioxide for carbonization for 7 days, spraying the surface of the solidified material after rapid carbonization twice, and the spraying time is 3 days to obtain a composite autotrophic denitrification and phosphorus removal filter material.
[0043] Example 3: A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: 20 parts of redispersible rubber powder and 15 parts of slow-release adsorbent are added to 65 parts of deionized water and stirred evenly to obtain a binder;
[0044] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 20 parts of a binder are added, granulated, aged and dried at room temperature to obtain slow-release adsorption particles;
[0045] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 1:1;
[0046] S4: adding the mixed slurry into the mold, drying, and curing the solidified material, placing the solidified material in a rapid carbonization box with 20% concentration of carbon dioxide for carbonization for 7 days, spraying the surface of the solidified material after rapid carbonization twice, and the spraying time is 3 days to obtain a composite autotrophic denitrification and phosphorus removal filter material.
[0047] Example 4: A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: adding 20 parts of redispersible rubber powder and 15 parts of slow-release adsorbent to 65 parts of deionized water and stirring evenly to obtain a binder;
[0048] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 20 parts of a binder are added, granulated, aged and dried at room temperature to obtain slow-release adsorption particles;
[0049] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 3:1;
[0050] S4: adding the mixed slurry into the mold, drying, and curing the solidified material, placing the solidified material in a rapid carbonization box with 20% concentration of carbon dioxide for carbonization for 7 days, spraying the surface of the solidified material after rapid carbonization twice, and the spraying time is 3 days to obtain a composite autotrophic denitrification and phosphorus removal filter material.
[0051] Example 5: A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: 20 parts of redispersible rubber powder and 15 parts of slow-release adsorbent are added to 65 parts of deionized water and stirred evenly to obtain a binder;
[0052] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 20 parts of a binder are added, granulated, aged and dried at room temperature to obtain slow-release adsorption particles;
[0053] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 3:1;
[0054] S4: adding the mixed slurry into the mold, drying, and curing the solidified material, placing the solidified material in a rapid carbonization box with 20% concentration of carbon dioxide for carbonization for 28 days, spraying the surface of the solidified material after rapid carbonization twice, and the spraying time is 7 days to obtain a composite autotrophic denitrification and phosphorus removal filter material.
[0055] Comparative Example 1: Preparation method of sustained-release adsorbent: 100 mg of chitosan microspheres were added to 1% v / v acetic acid solution, heated to 30°C and stirred for swelling, 100 mg of MgAl hydrotalcite was ultrasonically dispersed in 100 mL of deionized water to obtain a suspension; the suspension was added to the chitosan microsphere acetic acid solution, stirred for 24-26 hours, washed with deionized water, centrifuged, and vacuum dried to obtain a sustained-release adsorbent;
[0056] A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: adding 20 parts of redispersible rubber powder and 10 parts of slow-release adsorbent to 70 parts of deionized water and stirring evenly to obtain a binder;
[0057] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 12 parts of a binder are added, granulated, aged and dried at room temperature to obtain slow-release adsorption particles;
[0058] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 1:1;
[0059] S4: adding the mixed slurry into the mold, drying, and curing the solidified material, placing the solidified material in a rapid carbonization box with 20% concentration of carbon dioxide for carbonization for 7 days, spraying the surface of the solidified material after rapid carbonization twice, and the spraying time is 3 days to obtain a composite autotrophic denitrification and phosphorus removal filter material.
[0060] Comparative Example 2: A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: 20 parts of redispersible rubber powder and 10 parts of slow-release adsorbent are added to 70 parts of deionized water and stirred evenly to obtain a binder;
[0061] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 12 parts of a binder are added, granulated, aged and dried at room temperature to obtain slow-release adsorption particles;
[0062] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 1:1;
[0063] S4: adding the mixed slurry into a mold, drying, curing the solidified material, and spraying deionized water on the surface with a cloth for 7 days to obtain a composite autotrophic nitrogen removal and phosphorus removal filter material.
[0064] Comparative Example 3: A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material: S1: 20 parts of redispersible rubber powder and 10 parts of fulvic acid chelated iron ion modified hydrotalcite are added to 70 parts of deionized water and stirred evenly to obtain a binder;
[0065] S2: 40 parts of sodium thiosulfate, 30 parts of clay, and 30 parts of sulfur are added to 20 parts of deionized water and stirred evenly, 12 parts of a binder are added, granulated, aged and dried at room temperature to obtain adsorption particles;
[0066] S3: Add 250 parts of sulphoaluminate cement, 10 parts of ferrous sulfate, and 25 parts of silica fume to 85 parts of deionized water and stir evenly to obtain a concrete premix; mix the adsorption particles and the concrete premix evenly to obtain a mixed slurry; the mass ratio of the slow-release adsorption particles to the concrete premix is 1:1;
[0067] S4: Add the mixed slurry into the mold, dry it, cure the solidified material, spray deionized water on the surface for 7 days, and obtain the composite autotrophic nitrogen and phosphorus removal filter material
[0068] Experiment: The composite autotrophic nitrogen and phosphorus removal filter material prepared above was filled in an upflow anaerobic sludge reactor, and water was fed steadily and continuously through a peristaltic pump. The HRT was 9.6h, and tap water was added with an appropriate amount of NaNO 3 , KH 2 PO 4 The dynamic column test water was prepared to simulate the secondary treatment tail water of the domestic sewage plant. The inlet nitrate nitrogen concentration was 130mg / L and the total phosphorus concentration was 3mg / mL. The column was operated continuously for 3d and 20d to test the removal rate of nitrate nitrogen and total phosphorus in the sewage. The data are shown in Table 1 below.
[0069] Nitrate nitrogen removal rate 3d% Total phosphorus removal rate 3d% Nitrate nitrogen removal rate 20d / % Total phosphorus removal rate 20d% Example 1 89.2 90.2 96.7 98.9 Implementation of 2 89.5 90.8 96.9 99.2 Example 3 89.9 91.5 97.3 99.4 Example 4 90.3 92.0 97.7 99.6 Example 5 90.4 92.2 97.8 99.8 Comparative Example 1 80.2 86.7 86.7 95.6 Comparative Example 2 82.3 87.5 92.2 96.9 Comparative Example 3 89.2 90.1 88.3 96.0
[0070] Table 1 Denitrification and phosphorus removal technology effect data table
[0071] Conclusion: The composite autotrophic denitrification and phosphorus removal filter material prepared by the present invention has excellent technical effects of denitrification and phosphorus removal.
[0072] In Comparative Example 1, the surface of the hydrotalcite was not modified with fulvic acid and treated with iron ion chelation; in Comparative Example 2, the solidified material was not treated with alkali reduction; in Comparative Example 3, the fulvic acid chelated iron ion modified hydrotalcite was not treated with chitosan coating; as a result, the denitrification and phosphorus removal effect of the prepared composite autotrophic denitrification and phosphorus removal filter material was reduced.
[0073] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material, characterized in that: The following steps are involved: S1: adding redispersible rubber powder and slow-release adsorbent into deionized water and stirring evenly to obtain a binder; S2: adding sodium thiosulfate, clay and sulfur into deionized water and stirring evenly, adding a binder, granulating, aging and drying at room temperature to obtain slow-release adsorption particles; S3: adding sulphoaluminate cement, ferrous sulfate and silica fume into deionized water and stirring evenly to obtain a concrete premix; mixing the slow-release adsorption particles and the concrete premix evenly to obtain a mixed slurry; S4: adding the mixed slurry into a mold, drying, and curing the solidified material to obtain a composite autotrophic nitrogen removal and phosphorus removal filter material; The preparation method of the sustained-release adsorbent comprises the following steps: adding chitosan microspheres to a 1% v / v acetic acid solution, heating to 30-32° C. and stirring to swell, ultrasonically dispersing fulvic acid chelated iron ion modified hydrotalcite in deionized water to obtain a suspension; adding the suspension to the chitosan microsphere acetic acid solution, stirring for 24-26 hours, washing with deionized water, centrifuging, and vacuum drying to obtain a sustained-release adsorbent; The preparation method of chitosan microspheres comprises the following steps: adding chitosan to a 3% v / v acetic acid solution and stirring evenly to obtain an aqueous phase; adding paraffin to the aqueous phase, adding Span 80, heating to 40-45° C. and emulsifying for 1.5-2 hours under light-proof conditions, adding glutaraldehyde and continuing the reaction for 2-2.5 hours, washing the reaction solution with petroleum ether and isopropanol alternately for 3-4 times, and placing the reaction solution at 50-55° C. and vacuum drying for 24 hours to obtain chitosan microspheres; The preparation method of fulvic acid chelated iron ion modified hydrotalcite comprises the following steps: adding fulvic acid to 0.25M sodium hydroxide solution and stirring evenly to obtain sodium fulvic acid solution; adding magnesium chloride hexahydrate and aluminum chloride hexahydrate and stirring evenly to obtain metal ion solution; adding metal ion solution and 0.5M sodium hydroxide solution to the sodium fulvic acid solution under nitrogen atmosphere and stirring evenly, adjusting pH to 8-10, heating to 80-85°C and standing for reaction for 12-14h, centrifugation, collecting precipitation, washing with deionized water, vacuum freeze drying to obtain fulvic acid modified hydrotalcite; grinding the fulvic acid modified hydrotalcite and then ultrasonically dispersing it in deionized water, adding ferric nitrate solution, reacting for 2-2.5h, filtering, washing, grinding to obtain fulvic acid chelated iron ion modified hydrotalcite.
2. The method for preparing a composite autotrophic denitrification and dephosphorization filter material according to claim 1, characterized in that: The concentration of the suspension is 1 mg / mL; in the sustained-release adsorbent, the mass ratio of chitosan microspheres to fulvic acid chelated iron ion modified hydrotalcite is (1-1.5):
1.
3. The method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material according to claim 1, characterized in that: The concentration of the aqueous phase is 0.5-1 g / 100 mL; the volume ratio of aqueous phase to paraffin is 3:
1.
4. The method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material according to claim 1, characterized in that: The concentration of the sodium fulvic acid solution is 1-1.5 g / 100 mL; the concentration of the magnesium ion in the metal ion solution is 0.32-0.4 M / 100 mL; in the fulvic acid-modified hydrotalcite, the mass ratio of the metal ion solution solute to the sodium fulvic acid solution solute is 4:2; the concentration of the ferric nitrate solution is 1.5-2 g / 100 mL; in the fulvic acid-chelated iron ion-modified hydrotalcite, the mass ratio of the fulvic acid-modified hydrotalcite to the ferric nitrate solution solute is (3-4):
1.
5. The method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material according to claim 1, characterized in that: The components in the binder include 20-30 parts of dispersible rubber powder, 10-15 parts of slow-release adsorbent, and 55-70 parts of deionized water, calculated by weight.
6. The method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material according to claim 1, characterized in that: The components in the slow-release adsorption particles include, by weight, 20-60 parts of sodium thiosulfate, 30-40 parts of clay, 5-35 parts of sulfur, 12-20 parts of binder, and 15-25 parts of deionized water.
7. The method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material according to claim 1, characterized in that: The components in the concrete premix include 250-300 parts of sulphoaluminate cement, 10-12 parts of ferrous sulfate, 25-30 parts of silica fume, and 85-95 parts of deionized water in terms of mass fraction; the mass ratio of the slow-release adsorption particles to the concrete premix is (1-3):
1.
8. The method for preparing a composite autotrophic nitrogen removal and phosphorus removal filter material according to claim 1, characterized in that: The post-treatment curing process includes rapid carbonization of the solidifying material and spraying of the permanent setting liquid; wherein the rapid carbonization process includes placing the solidifying material in a rapid carbonization box with a carbon dioxide concentration of 20% for carbonization for 7-28 days; the permanent setting liquid spraying process includes spraying the surface of the solidifying material after rapid carbonization 2-3 times, and the spraying time is 3-7 days.
9. The composite autotrophic denitrification and dephosphorization filter material prepared according to the method for preparing a composite autotrophic denitrification and dephosphorization filter material according to any one of claims 1 to 8.
10. The use of a composite autotrophic denitrification and dephosphorization filter material according to claim 9, characterized in that: Used for sulfur autotrophic denitrification and phosphorus removal processes.
Citation Information
Patent Citations
Slow-release sulfur autotrophic denitrification biological filter material as well as preparation method and application thereof
CN116332329A